Effect of Growth Media and pH on Microalgal Biomass of Chlorella vulgaris for Biodiesel Production (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
The increased industrialization and overuse of natural resources for energy, such as fossil fuels, have led to the energy crises and environmental issues that plague the world in the twenty-first century. The production of biodiesel from algae has recently gained attention as a potentially useful alternative fuel that is both environmentally friendly and easy to obtain. In this work, the effects of various pH levels on algae biomass and oil production from Chlorella Vulgaris were studied. The growth of the biomass concentration was monitored using a spectrophotometer. The biomass of C. vulgaris obtained from the test was subjected to oil extraction using the chemical solvent method. Out of the five media compositions tested (MBG-11, BG-11, BBM, M8 and N8), MBG-11 recorded the highest biomass concentration at pH 8 (0.6 mg/L/D) and N8 recorded the least biomass concentration at pH 6 (0.49 mg/L/D). The highest percentage of oil was extracted from the C. vulgaris in BBM at pH 6 (31.22%) while the lowest oil was recorded in M8 at pH 8 (14.75%). In conclusion, the best medium for C. vulgaris biomass production was MBG-11 medium while the best medium for oil Production from this microalga was Bold Basal Medium (BBM).
Keywords: Algae; Growth Media; Biomass; Chlorella vulgaris; Biodiesel